Fibrinolysis and carcinoma of the prostate. Issue 3 (May 1965) - Swan, H. T.; Kerridge, D. F.
Abstract : In a series of 68 patients suffering from carcinoma of the prostate, plasma fibrinolytic activity has been found to be similar to that in control groups. Some comments have been made on the problem of fibrinolysis and bleeding associated with carcinoma of the prostate, with the suggestion that the part played by fibrinolysis has been over-emphasized.